Evaluation of Incest Cases: 4-Years Retrospective Study - Celbis, Osman; Altin, Ismail; Ayaz, Nusret; Bork, Turgay; Karatoprak, Serdar (Routledge Journals, Taylor & Francis Ltd, 2020)
Incest is specific type of sexual abuse. The aim of this study was to evaluate the sociodemographic data and examination findings of cases referred to our hospital as forensic court cases of incest, and to measure the effect on mental health disorders of the nature of the sexual abuse. Retrospective examination was made of the records of 40 cases of incest victims. Evaluation was made of the age, gender, incident suffered, the perpetrator, form of abuse, examination findings, and mental status. The cases comprised 36 girls and 4 boys. Without penetration sexual abuse was determined in 25 cases and with penetration sexual abuse in 15 cases. At least one mental health disorder was determined in 20 of the cases of simple sexual abuse and in 11 of the major sexual abuse type cases. The most frequently seen mental health disorder was post-traumatic stress disorder (PTSD) in 21 cases. Mental health disorders were determined in 77.5% of the incest cases in this study, at a greater rate 80% in cases of without penetration sexual abuse than in cases of with penetration sexual abuse 74.33%. Therefore, all cases of incest must be followed up carefully without differentiation of without or with penetration abuse.
Keywords: Incest; abuse; child sexual abuse; mental health